The Impact of Non-Current Assets on the Performance of Firms in Malaysian Construction Sector - Razman, Anuar; Mohamad, Jais; Michael, Tinggi (Human Resource Management Academic Research Society (HRMARS), 2021)
The aim of this study is to investigate on the relationship between non-current assets (NCA) for construction firms listed in Bursa Malaysia with firms’ performance. The efficiency of the firms’ NCA is measured by fixed assets turnover, asset tangibility, and total assets turnover mated with return on assets (ROA) and return on equity (ROE), both proxies for firms’ performance. The data collected and analysed in this research focused on the construction sector listed firms under Bursa Malaysia covering the period of 2011 to 2017. The methods employed in this research include descriptive analysis, correlation analysis, and fixed effects model to examine the research objectives. The quality of the data is tested by applying normality, multicollinearity, heteroscedasticity, and auto-correlation tests. The results of this study reveal that the fixed asset turnover (FATO) in the construction sector has a significant positive impact on both ROA and ROE. On the other hand, the total assets turnover (TATO) has a significant positive impact only on ROE while asset tangibility (ASTA) has no impact at all on both ROA and ROE. These findings are useful for governments, policymakers, and other stakeholders to develop effective policies, rules, or regulations in promoting economic productivity, growth, and best financing decision.